OUR EXPERIENCE IN USING MINIMALLY INVASIVE SURGICAL TREATMENT METHODS FOR FEMORAL FRACTURES - Ashirov M.U; Haydarov Samariddin Islom o'g'li; Isroilov Khushnudbek Erkin o'g'li; Sagdullayev Alibek Alisherovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Fractures of the trochanteric region of the femur are an urgent problem of modern traumatology, which is associated with an increase in the number of patients with injuries to this localization. Given the severity of the general condition of patients, the severity of osteoporosis and other unfavorable factors, it is necessary to more widely introduce minimally invasive, low-traumatic methods for treating fractures of the trochanteric region of the femur in elderly and older patients. In 2023-2024, we performed 147 closed percutaneous osteosynthesis operations for fractures of the trochanteric region of the femur, including 98 (66.6%) men, 49 (33.4%) women.